Hormone Therapy: A Potential Risk Factor Affecting Survival and Functional Restoration of Transplanted Lymph Nodes - Dong, Dong; Wang, Heng; Chen, Liang; Wang, Wei; Liu, Tianyi (Frontiers in Pharmacology, 2022)
Background: Transplantation of lymph nodes (LNs) is an increasingly popular option for treating lymphedema. Increasing evidence indicates an intrinsic correlation between estrogen signaling and the lymphatic system. We explored the effects of 17β estradiol and antiestrogen treatment (tamoxifen) on the survival and functional restoration of transplanted popliteal lymph nodes (PLNs). Methods: A total of forty-eight ovariectomized mice were divided into three groups of 16: OVX + E2 (treated with 17β-estradiol), OVX + TMX (treated with tamoxifen), and OVX (control; treated with olive oil as a solvent). After 2 weeks, PLNs were transplanted. Then, reconnections of lymphatic vessels were observed, and the morphology and survival of transplanted PLNs were evaluated 4 weeks after transplantation. T cells, B cells, lymphatic vessels, and high endothelial venules (HEVs) were subjected to immunofluorescence staining or immunohistochemical staining and quantified. Results: The percentage of lymphatic reconnections was 93.75% in the OVX + E2 group, 68.75% in the OVX + TMX group, and 75% in the OVX group. Surviving PLNs were observed in 16 of 16 in the OVX + E2 group, seven of 16 in the OVX + TMX group, and 13 of 16 in the OVX group. The mean size of PLNs in the largest cross section of the OVX + TMX group was significantly lower than that in the other groups. The distributions of B cells and T cells in surviving PLNs were similar to those in normal LNs. The ratio of dilated HEVs/total HEVs and density of lymphatic vessels in the OVX + E2 group were the highest among the three groups, whereas the lowest ratio and density were observed in the OVX + TMX group. Conclusion: Tamoxifen treatment might lead to cellular loss of transplanted LNs and interfere with the structural reconstruction and functional restoration, thereby inhibiting the survival of transplanted PLNs. Estrogen treatment facilitated the maintenance and regeneration of functional HEVs as well as lymphangiogenesis.